Effect of natural antioxidants and modified atmosphere packaging in preventing lipid oxidation and increasing the shelf-life of common dolphinfish (Coryphaena hippurus) fillets. Issue 1 (June 2015) - Messina, Concetta Maria; Bono, Gioacchino; Renda, Giuseppe; La Barbera, Laura; Santulli, Andrea
Abstract: We investigated the effects of natural antioxidants and modified atmosphere packaging (MAP) on the quality and shelf-life of Coryphaena hippurus (common dolphinfish) fillets. Fillets of the control group (CO) were simply placed on trays and not sealed. Fillets of the second group (MAP) were preserved in modified atmosphere (45% CO2, 50% N2, 5% O2 ), and fillets of the third group (MAP-AOX) were preserved by combining natural antioxidants from halophytes with modified atmosphere. All samples were stored in a refrigerator at −1 ± 0.5 °C for 18 days. Analyses were conducted at T0 and after 3, 6, 12, 15 and 18 days of storage. According to sensory tests and colour analyses, the fillets in the MAP and MAP-AOX groups maintained the best appearance. In the CO group, we observed a significant decrease of omega-3 polyunsaturated fatty acids (FAs) (P < 0.05), which indicates the oxidation of these FAs. FAs in the MAP and MAP-AOX groups were protected against oxidation. Further, lower peroxide value (PV) and malondialdehyde (MDA) content were observed in the MAP and MAP-AOX groups compared to the CO group. The sensory properties of the fillets were correlated with changes in FA content, PV and MDA content. Highlights: MAP and antioxidants from halophytes improve sensorial properties of fillets. MAP and antioxidants from halophytes protect PUFA n-3 from oxidation. MAP and antioxidants from halophytes reduce PV and MDA production.